THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND WORK STRESS ON JOB SATISFACTION OF CUSTOMER SERVICE OFFICER BAKTI PT BANK CENTRAL ASIA Tbk KCU PEKANBARU - R. Rudi Alhempi; Loveana Syaifora; Mulyani Rody Muin (Strategic Management Business Journal, 2023)
This research aims to determine the influence of emotional intelligence and work stress on job satisfaction of customer service officers at PT Bank Central Asia Tbk KCU Pekanbaru. This research is a quantitative research with emotional intelligence and job stress variables on job satisfaction. This study uses data collection techniques by distributing questionnaires. The number of samples in this study were all CSO Bakti employees of PT Bank Central Asia Tbk KCU Pekanbaru, totaling 47 employees. The data analysis technique used is multiple linear regression, coefficient of determination, and hypothesis testing. According to results of the study simultaneously that emotional intelligence and work stress affect the job satisfaction of CSO Bakti employees at PT Bank Central KCU Pekanbaru. Emotional intelligence and work stress contributed 79,6% to the job satisfaction of PT Bank Central Asia Tbk KCU Pekanbaru employee customer service officers, while the remaining 20.4% was accounted for by other variables not examined in this study.